Formulation and development of novel probiotic-loaded gel for the treatment of caffeine-induced anxiety - Pooja Verma, Rohit Dutt, Siraj Anwar (Journal of Applied Pharmaceutical Science, 2023)
This study shows the development of probiotics (Lactobacillus helveticus Strain NS8) loaded gel for the treatment of caffeine-induced anxiety. The formulation was developed by using Carbopol 980 by cold method and evaluated for clarity, pH, viscosity, spreadability, centrifugation, stability, and anti-anxiety efficacy in animal models. Caffeine was given to G1-G5 rats at a dosage of 25 mg/kg, i.p; while a probiotic formulation was given orally in G3 and G4 animal groups following caffeine. G5 group animals were applied with a probiotic topical gel to animals’ foreheads. Eddy’s hot plate, elevated plus maze test, and blood serum serotonin level were determined. F5 formulation showed excellent transparent, clear, and smooth characteristics with pH 5.3. The formulation showed desirable viscosity and spreadability for topical application. The animals (G5 group) treated with topical gel stayed longer on a hot plate (5.95 and 7.35 seconds). Probiotic topical gel-treated animals (G5 group) also showed a significant increase in time spent in open arms when compared to the anxiety control group. Animals treated with probiotic gel also showed significantly lower concentrations of serotonin levels. The stability studies conducted by F5 showed no significant changes in clarity, pH, and consistency. The gel formulation showed a comparable reduction in anxiety to the diazepam-treated animals and can be potentially used for the treatment of mild-moderate anxiety.
Keywords: Gel,